The politics of person reference third-person forms in English, German, and French - Truan, Naomi (Pragmatics & beyond ;, 2021)
"This book, the first systematic exploration of the third person in English, German, and French, takes a fresh look at person reference within the realm of political discourse. By focusing on the newly refined speech role of the target, attention is given to the continuity between second and third grammatical persons as a system. The role played by third-person forms in creating and maintaining interpersonal relationships in discourse has been surprisingly overlooked. Until now, third-person forms have overwhelmingly been considered as referring to the absent, i.e. to someone outside the communication situation, other than the speaker or the hearer: the "nonperson". By broadening the scope and finally integrating the third person, we come to understand The Politics of Person Reference fully, and to see the strategic, argumentative, and dialogical nature of the act of referring to other discourse participants, understood as the act of creating new referents"--